Time Token Implementation in Indonesian Elementary Mathematics: Evidence for Self-Confidence Enhancement - Rahmadhani, Wahyu; Nikmah Nurvicalesti (Journal of Innovation and Research in Primary Education, 2025)
Self-confidence represents a critical psychological factor influencing students' mathematics learning outcomes, yet many elementary students exhibit reluctance to participate actively due to fear of making mistakes and peer judgment. This quantitative study employed a pre-experimental design with one-group pretest-posttest pattern to examine the effectiveness of the Time Token learning model on fourth-grade students' self-confidence in mathematics learning at SD Negeri Windusari. All 28 fourth-grade students participated through saturated sampling technique. Data were collected using a validated self-confidence questionnaire (α = 0.87) comprising 20 items measuring four dimensions: belief in personal abilities, independent decision-making, positive self-concept, and willingness to express opinions. The intervention involved six mathematics lessons implementing structured turn-taking mechanisms through speaking tokens. Following the intervention, mean self-confidence scores increased substantially from 69 to 85, representing a 23.2% improvement. The proportion of students achieving strong confidence levels increased from 7% to 86%. All four measured dimensions demonstrated balanced development, ranging from 71% to 74%, with overall mean reaching 74% in the strong category. The Time Token model effectively enhanced students' self-confidence through structured, equitable participation opportunities that reduced psychological barriers to classroom engagement. These findings support the implementation of cooperative learning strategies that restructure classroom participation patterns to foster inclusive mathematics learning environments.